The public finances of Ireland - Oldham, C.H. (Statistical and Social Inquiry Society of Ireland, 1920)
It is the aim of this paper to notice as simply as possible the changes produced by the War conditions in the revenue and expenditure of Ireland: as these are exhibited in the annual returns popularly known as the "Treasury White Paper." There are always, of course, two White Papers; but one of them is a preliminary computation which leads up to the other. The principal White Paper is that entitled "Revenue and Expenditure (England, Scotland, and Ireland)," of which the latest issue is for the financial year ended March 31, 1919. (H.C. No. 163 of 1919, price 2d.) The other carries the clumsy title, "Imperial Revenue (Collection and Expenditure) (Great Britain and Ireland)"; it is mainly a computation by which the Revenues as actually "collected" in Great Britain and Ireland are adjusted so as to estimate the "true" Revenues really paid by the inhabitants of those two islands; but it also prints a retrospect of the figures for both Revenue and Expenditure over past years back as far as 1819.
Read Friday, January 23rd, 1920
Keywords: Irish revenue; Taxation; 314.15